Early mother-child interactions in low-income, single-mother families attending Chilean day nurseries, and cultural differences between German and Chilean dyads - Olhaberry Huber, Marcia (2015)
Each day there are more children being born and raised in low-income, single-parent homes, a condition being associated to a greater bonding vulnerability between mothers and young children, and to a negative effect on children’s mental health. This background information promoted a series of transversal and comparative studies on low-income, mother-child dyads. The global investigation includes two previous studies and two main studies, the first ones evaluating maternal stress and interaction quality, in single-parent and nuclear families. The results show a greater stress level and lower interactional quality in single-parent families. The two main studies evaluated mother-child dyads of single-parent families. The first one considered Chilean families with children attending and not attending public day nurseries, and the second one, Chilean and German families. Both of them evaluated infant psychomotor development, stress levels, maternal depressive symptomatology and mother-child interaction quality with the CARE-Index instrument. In the intercultural study were also evaluated interdependence and independence in the construction of self, ideology of sexual roles and tightness or looseness of social and family norms. The results of the first study show a positive effect by attending public day nurseries on infant psychomotor development, but a negative effect on mother-infant bonding quality. The negative effect on bonding quality increases when attendance to a day nursery starts before the child is 6 months old, just like the positive effect diminishes on infant psychomotor development, with the early start. The results of the second study show interactions of higher quality in Chilean dyads, and greater psychomotor development in German children, and higher scores on interdependence and tightness of family norms in Chilean mothers. There is an opportunity for reflection on the support strategies for early infancy in Chile, on vulnerable families, and the parenting models considering cultural contexts to interpret the results.
Keywords: Culture; Hochschulschrift